2021
DOI: 10.1002/jbm4.10441
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Initial Engagement of Intracellular Signaling Pathways by Parathyroid Hormone Receptor Ligands Teriparatide, Abaloparatide, and Long‐Acting PTH

Abstract: Multiple analogs of parathyroid hormone, all of which bind to the PTH/PTHrP receptor PTH1R, are used for patients with osteoporosis and hypoparathyroidism. While ligands such as abaloparatide, teriparatide (hPTH 1-34, TPTD), and long-acting PTH (LA-PTH) show distinct biologic effects with respect to skeletal and mineral metabolism endpoints, the mechanistic basis for these clinically-important differences remains incompletely understood. Previous work has revealed that differential signaling kinetics and recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 58 publications
0
31
0
1
Order By: Relevance
“…The authors of this study ( 102 ) indicated that their findings of no subtle differences between PTH (1–34) and abaloparatide in early actions that have been previously reported ( 98 100 ) might relate to limitations in design and sensitivity of assays. They also consider the possibility that the differences noted by others in clinical studies might be related to pharmacokinetic or other factors ( 102 ).…”
Section: Persistent Activation Of Adenylyl Cyclase In Endosome By Pth and Pthrp Peptidesmentioning
confidence: 69%
See 3 more Smart Citations
“…The authors of this study ( 102 ) indicated that their findings of no subtle differences between PTH (1–34) and abaloparatide in early actions that have been previously reported ( 98 100 ) might relate to limitations in design and sensitivity of assays. They also consider the possibility that the differences noted by others in clinical studies might be related to pharmacokinetic or other factors ( 102 ).…”
Section: Persistent Activation Of Adenylyl Cyclase In Endosome By Pth and Pthrp Peptidesmentioning
confidence: 69%
“…The lack of prolonged effect on cAMP production by PTHrP (1–36) or abaloparatide was considered to be due to reduced internalization of receptor, and faster recycling possibly caused by endosomal pH sensitivity ( 99 , 100 ). Abaloparatide, which had been developed as a new analog ( 101 ) for therapeutic use in osteoporosis, is identical to PTHrP in its first 21 residues, but has 8 residues different from PTHrP between 22 and 34, and is equipotent with PTH peptides in the standard bioassay of total cell cAMP generation in target cells ( 79 , 100 , 102 ).…”
Section: Persistent Activation Of Adenylyl Cyclase In Endosome By Pth and Pthrp Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pleiotropic in its downstream coupling, PTH1R signals primarily via Gs, but can also couple to Gq 18 , G12/13 19 and Gi 20 , and interacts with and signals via β-arrestins 21,22 . The two endogenous agonists, parathyroid hormone (PTH) and parathyroid hormone-related peptide (PTHrP), trigger PTH1R activation with similar kinetics and specificity for the various intracellular pathways [23][24][25] . However, PTH can induce prolonged signalling from intracellular sites, while PTHrP signals exclusively from the cell surface 26 .…”
Section: Introductionmentioning
confidence: 99%